Shaping Spectra within Optical Fibers: Embedding high‐resolution spectrometers into the cores of optical fibers. Issue 2 (12th March 2019) - Waltermann, Christian; Guehlke, Philip; Koch, Jan; Schippers, Wolfgang
Abstract: A unique fiber‐integrated diffraction grating enables a new kind of ultra miniature high‐resolution spectrometer. Within, all components for optical imaging are encoded directly leading to an outstanding ratio of optical resolution to build size. The entire design comprises only two aligned parts and allows a cost‐effective, customizable production, and robust spectrometers. As an exemplary application we present a compact interrogation system for fiber Bragg grating sensors.